2018
DOI: 10.1016/j.lfs.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Defining the molecular signatures of human right heart failure

Abstract: This work provides some of the first analyses of the molecular heterogeneity between human RV and LV tissue, as well as key differences in human disease (RVF secondary to pulmonary hypertension and LVAD mediated RVF). Our transcriptional data indicated that inflammatory pathways may be more important in RV tissue, and changes in FIGF and CTGF supported this hypothesis. In PAH RV failure samples, upregulation of FBN2 and CTGF further reinforced the potential significance that altered remodeling and inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Next, we found the functional enrichment of the hub genes associated with HF or ISCH or CMP were similar with those for the blue module. Williams and his colleagues found that SMOC2 was differentially expressed in failing right ventricular, and was potential targets for further study on HF [42]. A study revealed that SMOC2 could modulate fibroblast proliferation and extracellular matrix deposition [43].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we found the functional enrichment of the hub genes associated with HF or ISCH or CMP were similar with those for the blue module. Williams and his colleagues found that SMOC2 was differentially expressed in failing right ventricular, and was potential targets for further study on HF [42]. A study revealed that SMOC2 could modulate fibroblast proliferation and extracellular matrix deposition [43].…”
Section: Discussionmentioning
confidence: 99%
“…Above all, our study stands out for its unbiased, comprehensive approach to identifying molecular pathophysiological signaling specific to the failing RV. Prior transcriptomic analyses of animal models and human tissue have relied on differential-expression and pathway analyses without subsequent experimental and mechanistic validation studies of proposed molecular signatures of RVF (13)(14)(15)(16)(17)(18)(19)(20). Although single-gene and differential-expression analyses are powerful tools, there are a number of advantages with WGCNA (59).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have been challenged by limitations of commonly used animal models that were developed to study pulmonary vascular disease rather than RV dysfunction or biventricular HF. Some studies have sought to identify molecular signatures of RVF, using animal models (13)(14)(15)(16)(17) or human tissue (18)(19)(20). Most of these were limited to animal models or patients with RV dysfunction but not RVF (13,14,16,18,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both intramembranous and alveolar bone repair also require de novo coupling with angiogenesis 38 wherein SMOC2 functions in vascular patterning may be augmented during injury-induced revascularization 14 . SMOC2 is differentially increased in failing human heart, potentially marking injury-induced myocardial ischemia and/or fibrosis 39 . Smoc2 mutants could serve as a novel model to understand tissue repair, particularly in non-invasive therapy as anti-inflammatory (ibuprofen) treatment was shown to normalize defects in our experimental system.…”
Section: Smoc2 Is Required For Bone Repair and During Periodontal Agingmentioning
confidence: 99%